The enlightened city. (August 2022) - Beaumont, Justin
Abstract: Postsecularity, or the nature of the reflexive questioning or destabilization of the secular, remains a highly contested and problematic notion across the social sciences and humanities. Most perspectives share profound disappointment in the institutions of liberal democracy, requiring us to rethink the grounds for ethical and political action in post-political, -democratic, and -truth times. I argue with reference to select illustrative cases that one possible value of postsecularity rests in the notion of the enlightened city that emanates from three broad lines of inquiry: (1) new geographies of religion and postsecularity with implications for decolonial urban theory and the commons; (2) Frankfurt School-inspired messianic critical theory, reflexive secularization, and decolonial urban postsecularity; and (3) reflexive humanization, perceived "impossibility" of wholeness, and critical discourse on the Anthropocene. Rather than repeat the all-too-familiar dangers of Enlightenment rationalism, this approach stresses an immanent transcendent overlapping of ethical and political imperatives beyond the classical separation of life and politics, "planetary urbanization" and zone of indistinction providing the canvas from which postsecular processes unfold, and new subject formation that reconciles radical differences towards a higher unity and confronts injustices in more inclusive and humane ways.